Myeloid Sarcoma - a diagnostic challenge in pediatric practice. - Nageen, Tabinda; Muhammad, Syed Zaki; Imam, Uzma (Journal of the Pakistan Medical Association, 2022)
Myeloid Sarcomas are rare tumors of myeloid origin that may infiltrate multiple sites of the body. They may precede acute myeloid leukemia or present without it. It has nonspecific manifestations and presents as a diagnostic and therapeutic challenge owing to the limited literature that reports consensus on diagnostic and treatment strategies. Immunohistochemistry is of significance in identifying the disease and acute myeloid leukemia protocols of systemic therapy remain the mainstay of treatment. Our report of an 11 years old child with myeloid sarcoma aims to add to the limited existing literature and describe the varied presentation and sites of involvement.